Eksistensi Gotong Royong sebagai Pilar Penguatan Identitas Nasional di Indonesia - Nova, Mellynda Az Zahra (Maliki Interdisciplinary Journal, 2025)
The culture of mutual cooperation has long been an inseparable part of Indonesia’s national identity and is deeply rooted in people’s lives. As a cultural heritage, mutual cooperation reflects the character of the nation that prioritizes togetherness, solidarity, and concern for others. In the context of national identity, this culture functions as a pillar that strengthens the unity and integrity of the nation, even though it is faced with the challenges of globalization and changing times that have the potential to erode traditional values. This study emphasizes the importance of preserving mutual cooperation as local wisdom that is not only an element of culture, but also a foundation for social, economic, and political development in Indonesia. The younger generation plays a major role in internalizing and reviving the values ​​of mutual cooperation, so that this culture remains relevant and becomes the foundation for a strong Indonesian national identity.